Decrease of LDL Cholesterol Through The Increase of HDL Cholesterol by Administering Garcinia mangostana L. Peel Extract in White Mice - As'ari, Hasyim (Folia Medica Indonesiana, 2021)
Highlight: • Ethanol extract of Garcinia mangostana L. peel reduce malondialdehyde. • Garcinia mangostana L. peel extract can increase non-radical products which impact in decreasing LDL cholesterol and increasing HDL cholesterol. Abstract: Atherosclerosis contributes to coronary heart disease which may lead to fatality. High cholesterol consumption, stress, and smoking can increase LDL cholesterol in the blood. Consumption of unsaturated fats, high fiber foods, exercise, quitting smoking, losing weight, and giving hypolipidemic drugs, especially herbs, can increase HDL cholesterol and decrease LDL cholesterol. Garcinia mangostana L. peel extract can decrease LDL cholesterol by increasing reverse HDL cholesterol transport to the liver. The study used post test control group design. This study was experimental laboratory research with population of hypercholesterolemic male white mice aged 3-4 weeks with 100-200 grams weight. The HDL and LDL cholesterol data were collected through an enzymatic method by spectrophotometer. This study used analysis of variance (Anova) with significance level of α <0.05. The experiment divided the subjects into positive and negative control groups with dosage variations of 50, 150, 250, and 350 mg/kgBW. Examination of hypercholesterolemia in white mice was conducted on the 8th day. The examination of HDL and LDL cholesterol given peel extract of Garcinia mangostana L. was conducted on the 22nd day. The analysis showed that giving Garcinia mangostana L. peel extract for various dosages could significantly decrease LDL cholesterol and increase HDL cholesterol (p <0.05). Peel extract of Garcinia mangostana L. that contained mangosteen could increase non-radical products that could prevent the transfer of ester cholesterol from HDL to VLDL which impact in increasing HDL cholesterol and decreasing LDL cholesterol.